The Role of Monosodium Glutamate in Neural Crest Cell Migration Impacts Congenital Heart Defects and the Protective Effect of Folic Acid in Chick Embryo Models - Pintarasri, Suriyan; Santiparadon, Manutsanun; Kamnate, Anussara; Ebuh, Fatin; Nalinbenjapan, Warisra; Saising, Firdaws; Apitanapipat, Kamonchanok; Thippheng, Nuttakrita (Trends in Sciences, 2025)
Introduction: Congenital heart defects are among the most common birth anomalies, characterized by malformations of cardiac structures such as the pharyngeal arches, aorticopulmonary septum, and outflow tract. Disruptions in neural crest cell function during embryogenesis have been also associated with congenital heart defects. This study investigates the teratogenic effects of monosodium glutamate on the critical signaling pathways of cardiac neural crest cells in cardiac morphogenesis, and folic acid mitigates this adverse effect in chick embryo models. Materials and methods: Using a combined network pharmacology and molecular biology approach, we identified molecular targets potentially associated with monosodium glutamate-induced congenital heart defects. Fertilized chick eggs were divided into control, monosodium glutamate exposure and folic acid treatment groups, and the effects on cardiac tissue structures were evaluated in 3 and 6-day-old embryos. Wingless-related integration site and bone morphogenetic protein signaling proteins were analyzed via immunostaining and immunoblotting techniques, while homocysteine levels were quantified using an ELISA assay. Results and discussion: These findings revealed that the molecular targets shared through network pharmacology and molecular docking analyses were closely linked to neural crest cell function. Monosodium glutamate exposure resulted in a significant reduction in neural crest cell populations and downregulation of Wingless-related integration site and bone morphogenetic protein signaling protein expression (p < 0.05). Additionally, homocysteine levels were controlled by monosodium glutamate exposure, suggesting a metabolic influence on cardiac development. Treatment with folic acid mitigates this adverse effect by lowering homocysteine levels. Conclusion: In conclusion, this study provides novel evidence that monosodium glutamate-induced teratogenesis disrupts the protein signaling molecules and metabolic pathways critical to embryonic heart development. This leads to congenital heart defects analogous to those observed in humans. These insights offer a foundation for understanding the impact of environmental teratogens on congenital heart anomalies and the role of neural crest cell-associated signaling pathways in cardiac morphogenesis. Moreover, the treatment with folic acid mitigates an adverse effect on cardiac morphogenesis by lowering homocysteine levels. HIGHLIGHTS MSG exposure disrupts cardiac neural crest cell function by reducing populations and downregulating Wnt and BMP signaling pathways, contributing to congenital heart defects. Structural abnormalities, including thinner ventricular walls, impaired septation, and blood congestion, were observed in MSG exposure embryos, highlighting its teratogenic impact on heart development. Elevated homocysteine levels in MSG exposure embryos suggest a metabolic mechanism linking MSG exposure to the increased risk of CHDs, and treatment with folic acid mitigates this adverse effect by lowering homocysteine levels. GRAPHICAL ABSTRACT